Diagnosis of diabetes: HbA1c versus WHO criteria - Manley, S; Nightingale, P; Stratton, I; Sikaris, K; Smith, J; Cramb, R; Gough, S (2010)
The authors compared the diagnosis of type 2 diabetes using an HbA 1c cut-off point of ≥6.5% (≥48 mmol/mol) with current World Health Organization (WHO) criteria involving fasting plasma glucose and an oral glucose tolerance test. Diabetes was confirmed in 35% of Australian and 49% of UK participants using WHO criteria and a similar prevalence was obtained using HbA1c - 31% and 46%, respectively. Using HbA1c levels alone for diagnosis does not define the same people with diabetes as the WHO criteria. A considerable number of participants (38% of Australian and 49% of British) diagnosed with diabetes by WHO criteria would not have been diagnosed using a single HbA1c test. More consideration of the use of HbA 1c as a screening test for diabetes is required.